Radical decarboxylation strategies for the synthesis of nitrogen-containing heterocycles - Mazodze, Crispen Munashe (Department of Chemistry, 2023)
Nitrogen-containing heteroaromatics are ubiquitous in nature. In addition, 75% of FDA-approved drugs currently on the market are based on these compounds, establishing them and their analogues as a primary source of therapeutic agents in the pharmaceutical industry. The structural complexity exhibited by these nitrogen-based moieties necessitates the development of innovative strategies that demand mastery beyond routine and traditional organic chemistry that most synthetic chemists typically cultivate. The second chapter of this thesis describes the use of novel delayed radical precursors in Mn (OAc)3·2H2O mediated oxidative radical cyclization-fragmentation-dimerization processes from Banilides. The first part presents a sequential oxidative radical cyclization-decarboxylative-dimerization process from β-oxoacids, forming three bonds in a one-pot manner. This approach was successful with a diverse range of 3,3′-bisoxindoles substrates obtained in up to 96% yield. The second part of chapter two details a complementary and closely related sequential one-pot oxidative radical cyclization-deformation-dimerization process from β-oxoanilides, this motion was also applicable to a wide array of 3,3′-bisoxindoles with up to 98% yield. There are no clear-cut distinctions between the decarboxylative and deformylation approaches as they appear to be highly complementary to each other. The chapter concludes with a further demonstration of the utility of this methodology, in the formal synthesis of the calycanthaceae alkaloid, (±)-folicanthine via to the best of our knowledge the shortest linear route. The third chapter of this thesis describes a general extension of the second chapter, which involves an atom-efficient silver-catalysed double decarboxylative strategy for the one-step synthesis of quinolin2-ones. This is achieved via an oxidative radical addition–cyclisation–elimination cascade sequence of oxamic acids to acrylic acids, mediated either thermally or photochemically. The reaction proved to be successful with a wide range of 32 quinolin-2-ones synthesized in of up to 84% yield. The method features an elegant double-disconnection approach, which constructed the quinolin-2-one core through the formal and direct addition of a C(sp2)–H/C(sp2)–H olefin moiety to a phenyl formamide precursor. The theme of the thesis is centred around the synthesis of nitrogen-containing heteroaromatics using facile and efficient protocols that offer catalyst, atom and energy efficiency, while also providing substantial economic advantages. Additionally, the thesis presents systematic and in-depth mechanistic studies on both developed protocols to support and offer compelling evidence for the proposed mechanistic cycles. These studies provide insights into the reaction pathways and help establish a more comprehensive understanding of the radical synthetic pathways.